2019
DOI: 10.4028/www.scientific.net/jnanor.56.80
|View full text |Cite
|
Sign up to set email alerts
|

Fish Gelatin Antimicrobial Electrospun Nanofibers for Active Food-Packaging Applications

Abstract: A protein-based electrospun nanofiber from cold water fish gelatin (FG) including bovine lactoferrin (L) as an antimicrobial substance for food packaging applications was developed. Various amounts of L (0, 5, 10, 15, and 20%) were incorporated into FG electrospun nanofibers in order to test antimicrobial activity by disc diffusion method against Pseudomonas fluorescens, Acinetobacter johnsonii, Aeromonas hydrophila, Flavobacterium psychrophilum, Shewanella putrefaciens, and Escherichia coli commonly cause pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Gelatin, with its good biocompatibility and biodegradation, attributed to its composition of 14% hydroxyproline, 16% proline, and 26% glycine [8], has been widely applied in many biomedical applications such as wound dressings and tissue engineering [9,10]. Gelatin has been incorporated with polysaccharides [11], chitosan [12], silk fibroin [13], and polycaprolactone (PCL) [14] to be electrospun, and the resulting morphologies, properties, and applications have been studied. Raut et al demonstrated that the addition of gelatin could improve the hydrophilicity, biocompatibility, and blood compatibility of the polyurethane surface [15].…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin, with its good biocompatibility and biodegradation, attributed to its composition of 14% hydroxyproline, 16% proline, and 26% glycine [8], has been widely applied in many biomedical applications such as wound dressings and tissue engineering [9,10]. Gelatin has been incorporated with polysaccharides [11], chitosan [12], silk fibroin [13], and polycaprolactone (PCL) [14] to be electrospun, and the resulting morphologies, properties, and applications have been studied. Raut et al demonstrated that the addition of gelatin could improve the hydrophilicity, biocompatibility, and blood compatibility of the polyurethane surface [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent times, oil-dependent polymeric nanocomposite films have a wide range of uses, including, pharmaceutical packaging and biomedical equipment [ 49 , 50 ]. These nanoparticles exert viable and potent antimicrobial properties against various drug resistant microbes [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the addition of natural plant extracts as antioxidants and antibacterial to food packaging prevents oxidative damage and bacterial contamination during storage. Effective ingredients used for AP purposes to date include polyphenol-rich plant extracts from Aloe vera [74], green tea [57], curcumin [64], pomegranate peel [78], glycerol monolaurate [93], lactoferrin [79], sage [84] and essential oils such as chrysanthemum [60], thyme [66,73,75], chamomile [72], peppermint [72], oregano [61], and also, some nanoparticles include silver nanoparticles (AgNPs) [63], zinc oxide (ZnO) nanoparticles [80] and TiO 2 nanoparticles [83,88] that have been studied in many products with different polymers with antioxidant and antibacterial properties. In Table 2, the properties of these active ingredients and the other agents like gums and peptides, along with the material of NFs, have been summarized as bioactive electrospun food packaging systems.…”
Section: Bioactive Electrospun Food Packagingmentioning
confidence: 99%